Switching from Dupilumab to Abrocitinib in Patients with Moderate-to-Severe Atopic Dermatitis: A Podcast Article - Vivian Y. Shi (Dermatology and Therapy, 2025)
Abstract As the number of systemic agents available for the treatment of moderate-to-severe atopic dermatitis (AD) continues to increase, it is likely that patients may need or want to switch from one treatment to another. Owing to differences in the mechanism of action, the systemic agents abrocitinib (an oral Janus kinase 1-selective inhibitor) and dupilumab (an injectable interleukin 4 alpha antagonist) are associated with distinct efficacy and safety profiles. Two recent publications have examined the efficacy and safety of long-term abrocitinib in patients previously treated with dupilumab. In this podcast article, two dermatologists discuss the management of moderate-to-severe AD and highlight factors to consider before changing therapies in the context of these recent studies, focusing on switching from dupilumab to abrocitinib treatment. Below is the link to the electronic supplementary material. Supplementary file1 (MP4 173881 KB)